Antiviral activity and Antioxidant role of phenolics from Sophora interrupta Bedd in NDV induced oxidative stress in chickens - Cherukupalle Bhuvaneswar,; Pappithi Ramesh Babu,; Chintha Venkata Ramaiah,; Gandham Sandeep,; Wudayagiri Rajendra, (International Journal of Phytomedicine, 2017)
The present investigation is taken up to evaluate the antiviral efficacy of phenolics isolated from Sophora interrupta Bedd and their antioxidant role in the brain and lungs of chicken during Newcastle disease virus (NDV) induced oxidative stress. The activity levels of selected antioxidant enzymes such as superoxide dismutase (SOD), catalyse (CAT), glutathione peroxidase (GPx), glutathione reductase (GR) and glutathione-S-transferase (GST) levels were significantly decreased in brain and lung tissues of NDV infected animals over controls causing oxidative stress. In addition, histopathological alterations disclosed that lungs of NDV infected chicken were affected severely as evidenced by the alterations in alveolar cell morphology, congestion, necrotic and degenerative changes whereas degeneration of Purkinje cells, neuronal necrosis, degeneration in myelin sheath and compression of cells were observed in the brain of NDV infected chickens. These reduced antioxidant defence mechanisms and histopathological abnormalities were restored to normal when chicken were pre-treated with the phenolics isolated from Sophora interrupta Bedd at the dose of 300 mg/Kg Bw/day for one week. Pre-treatment with the phenolics isolated from the above medicinal plant also caused significant reduction in the titre levels of NDV. These results suggest that pre-treatment with the phenolics isolated from Sophora interrupta Bedd exhibited significant antiviral activity and thus the plant extract may be used as a prophylactic treatment for the prevention of NDV infection in chicken.